Cash plus programming and intimate partner violence: A qualitative evaluation of the benefits of group-based platforms for delivering activities in support of the Ethiopian government's Productive Safety Net Programme (PSNP) - Buller, Ana Maria; Pichon, Marjorie; Hidrobo, Melissa; Mulford, Michael; Amare, Tseday; Sintayehu, Wastina; Tadesse, Seifu; Ranganathan, Meghna (BMJ, 2023)
Objectives: Intimate partner violence (IPV) is a public health challenge but there is evidence that cash and cash ‘plus’ interventions reduce IPV. An increasingly popular design feature of these kind of interventions is the group-based modality for delivering plus activities, however, evidence of the mechanisms through which this modality of delivery impacts IPV is limited. We explore how the group-based modality of delivering plus activities that complemented the Government of Ethiopia’s Productive Safety Net Programme contributed to modifying intermediate outcomes on the pathway to IPV. Design: Qualitative study using in-depth interviews and focus group discussions between February and March 2020. Data were analysed using a thematic content and gender lens approach. Findings were interpreted, refined and drafted in collaboration with our local research partners. Setting: Amhara and Oromia regions in Ethiopia. Participants: In total 115 men and women beneficiaries from the Strengthen PSNP4 Institutions and Resilience (SPIR) programme took part in the study. Fifty-eight were interviewed and 57 took part in 7 focus group discussions. Results: We found that Village Economic and Social Associations—through which SPIR activities were delivered—improved financial security and increased economic resilience against income shocks. The group-based delivery of plus activities to couples appeared to enhance individual agency, collective power and social networks, which in turn strengthened social support, gender relations and joint decision-making. Critical reflective dialogues provided a reference group to support the shift away from social norms that condone IPV. Finally, there appeared to be gender differences, with men highlighting the financial benefits and enhanced social status afforded by the groups, whereas women’s accounts focused primarily on strengthened social networks and social capital. Conclusion: Our study offers important insights into the mechanisms by which the group-based delivery of plus activities affects intermediate outcomes on the pathway to IPV. It underscores the importance of the modality of delivery in such programmes, and suggests that policy-makers should consider gender-specific needs as men and women might differentially benefit from interventions that enhance social capital to generate gender transformative impacts.